Analysis of The Composition Chemical Flours "Mulu Bebe" (Musa acuminata) Modification North Halmahera Indigenious as a Prebiotic Food Source - Lumba, Ronal; Yusniar, Masitah (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 7 No 1 (2020): Scientific Journal of Food Technology (March), 2020)
“Mulu bebe” banana ( Musa acuminata ) is one of the tropical fruit commodities that has the potential in Indonesia, specifically the North Halmahera region has a very high opportunity as a food diversification material. The aim of the study was to determine the chemical composition of "mulu bebe" banana flour produced through the modification of spontaneous fermentation and cooling heating as a prebiotic food source. This study using factorial Randomized Complete Design (CRD) with three replications. The first factor was the duration of spontaneous fermentation of 0, 12, 24 and 36 hours and the second factor was the length of heating, namely 0 and 45 minutes then continued with cooling at 4 o C for 24 hours. The results of the chemical composition analysis of “mulu bebe” banana flour with spontaneous fermentation conservation and safety supplements against the chemical composition of banana flour produced were 7.21-10.68% water content, 1.84-2.74% ash content, crude fiber 0, 57 -2.61%, fat content from 0.93-1.44%, protein content from 3.55 to 4.21%, content from 45.63 to 69.24%. Changes in the chemical composition of the banana flour, caused by the fermentation process and the addition of supplements to sliced bananas before drying. This study obtained banana flour products which are low in fat, protein and carbohydrate content which indicated that the bebe banana flour products produced by contained resistant starch (RS) as prebiotic food source.